REPRESENTATION OF KIRATARJUNIYAM IN THE TEMPLE SCULPTURES OF KADAPA DISTRICT - Rao, K. Mrutyunjaya (International Journal of Research -GRANTHAALAYAH, 2025)
The paper describes the narrative episode of the famous Kiratarjuniyam in the temple sculptures of Kadapa district. This theme is commonly found at Chilamkuru, Attirala, Pushpagiri, and Animela in the Kadapa district but varies in depiction. Its significance is in terms of sculptural carvings in seven panels. The Kiratarjuniyam episode was rendered with great skill and stood out for the master’s skills in sculptures. Though the story is depicted in limited panels, it is the best narrative in the whole sculptural heritage in Kadapa. Proportions and narrations and compositional values are discussed to unfold the aesthetics of the temple sculptures. The author tried to study the variations in the theme depicted in the temples of the Kadapa region. The aesthetic evaluation of the compositional and carving skills of the sculptors is to be considered subject to the limitation of space and place of execution.